Predlog metodologije za razmejevanje kmetijskih in primestnih krajin v Sloveniji ter prostorska določila za določanje gozdov s poudarjeno funkcijo ohranjanja biotske raznovrstnosti - Firm, Dejan (Gozdarski vestnik, 2017)
In this article we present a new methodology for delineating agricultural or suburban landscapes and, at the same time, we prepared a set of simple indicators (forest cover level, number of patches, shape and size of forest patches, spatial distribution and connection of forest patches). By the use of these indicators and some common sense, we have found out, that the majority of thus acquired agricultural landscapes in western, northern, and southern Slovenia is surrounded by the forest(ed) matrix, which along with relatively sufficient forest cover of the landscapes themselves enables passage of species between matrix and agricultural landscapes. In the central Slovenia, in Gorenjska, and in the eastern Slovenia we encounter fragmentation of once uniform agricultural landscapes due to highways and, partly, damming of the Sava and Drava rivers. In these landscapes, findings, we get by evaluating of indicators of the landscapes% shape and size, landscape%s forest cover or density of patches, size class and shape of forest patches are important for the diversity evaluation.
Keywords: forest patches; gozdne zaplate; kmetijska krajina; agricultural landscapes; regulations for forest clearing; določila krčitev gozdov; biodiversity; krčitev gozdov; biotska raznovrstnost; Slovenia; Slovenija